Typological structure of pine forests in Central Polissia - Andreieva, O. Yu.; Ivaniuk, I. D.; Ivaniuk, T. M.; Budnik, I. P. (Forestry and Forest Melioration, 2020)
Introduction During recent decade the health of pine forests has deteriorated which resulted in an increase in sanitary felling and new outbreaks of stem pests in many regions, in particular in Central Polissia. Climate change, in particular a lowering of groundwater table, was reflected in the weakening of pine forests and availability of forest plots both for growing certain species and harmful insects’ attacks. In a study of the distribution of foci of forest decline, it was shown that mixed stands, in particular pine and birch, are more resistant than pure pine stands to various negative factors, namely to the bark beetle attacks. Therefore, one of the ways to increase forest resilience is to identify reserves for the growing mixed stands. The aim of the research was to reveal the special aspects of forest area distribution in certain forest enterprises by forest site conditions, particularly the area of all Scots pine stands and pure Scots pine stands. Materials and Methods The Ukrderzhlisproekt Production Association database (by 1.01.2011) for 14 State Forest Enterprises in Zhytomyr Region was analysed. The data on changes in the area of clear felling in the region were taken from the reports of Zhytomyr Regional Administration of Forest and Hunting Management as well as of the State Specialized Forest Protection Enterprise Vinnytsialisozahyst for 2011–2019. Results and Conclusions The study showed that pine stands comprise from 31.5 to 87.7 % of the total area covered by forest vegetation in the forest fund of the analysed state forestry enterprises in Zhytomyr Region characteristic for Central Polissia. Fresh and moist fairly poor and fairly fertile forest site conditions prevail. The proportion of pure pine stands averages 23.9% of the area covered by forest vegetation and 37.3% of the area of pine stands. At that, the potential proportions are 7.7 and 11.2% respectively. The largest area of pure pine stands can be established in the forest fund of Narodytske, Ovrutske, Slovechanske, and Luhynske Forest Enterprises in the northern part of the region and Malynske Forest Enterprise in the southern part. The difference between the actual and theoretically possible area of pure pine stands in the forest fund of all analysed forest enterprises makes 5,909.5 ha. The maximum differences (8,919–10,017 ha) were determined for the forest fund of the Slovechanske, Narodytske and Olevske Forest Enterprises in the northern part of the region and Radomyshlske Forest Enterprise in the southern part of the region. The calculations allow increasing the resilience of pine stands in the region by enlarging the area of mixed pine stands at sites with proper forest conditions. At the same time, the possibility that moisture conditions can shift as a result of recent climate change should be taken into account. 5 Tables, 16 Refs. Key words: types of forest site conditions, trophotop, hyhrotop, pure pine stands.